Higher School Faculty Staff in the Era of Digitization: Teaching’s Activities Transformation and Problems of Professional Adaptation - Evdokimova, M.V. (KnE Social Sciences, 2021)
This article is devoted to the study of the higher educational institutions teachers’ professional adaptation problem in the context of digitalization. The purpose of this research is to analyze the main changes in the higher education staff’s professional activities due to the digitalization of education, as well as the problems of a university’ staff adaptation to these changes. The relevance of the study is justified by the fact that the effectiveness of the implementation of information and digital technologies in the educational process largely depends on the success of the university staff’s professional adaptation. The main methods of empirical research were students’ questioning and semi-formalized interviews with the university staff. The study was carried out on the basis of Khakass State University in 2019 with the financial support of the Russian Foundation for Basic Research as part of scientific project No. 18-011-00681 A. 500 students and 39 teachers were interviewed (N = 539). The study has found that teaching in digitalization is experiencing a serious sociocultural transformation in addition to technological changes. Information and digital technologies form new principles for organizing the educational process, new forms of teacher communication with students and colleagues, new sociocultural environment of the university and, ultimately, a new role for the teacher in modern education. The study revealed that the digitalization of education entailed significant changes in all types of a university staff’s professional activities — pedagogical, scientific and scientific-methodological. The main difficulties in the university staff’s professional adaptation are associated with insufficient material and technical equipment of universities, constantly increasing actual load, low level of information culture and computer literacy. As a result of the study, it was found that university staff misunderstands the very phenomenon of education digitalization, referring to informatization and computerization, that, of course, prevents the successful implementation and effective use of digital technologies in education. Keywords: teacher of higher education, digitalization of education, professional adaptation of teachers